Faktor-Faktor dalam Koordinasi Lintas Sektoral Pengelolaan Drainase di Kota Semarang - Irfan Ramdhany; Titik Djumiarti (Journal of Public Policy and Management Review, 2016)
This research was to study and analyze the coordination of drainage management in Semarang city and also to determine the factors in intersectoral coordination of drainage management in Semarang city. Drainage management in Semarang is managed by intersectoral SKPD. This research is a qualitative descriptive which data collected through interviews, literatures, and study documents. Information was collected from BAPPEDA, Dinas PSDA & ESDM, DTKP, and DKK. Researcher used indicators of coordination and factors of intersectoral coordination to examine coordination of drainage management in Semarang. The result showed that factors in intersectoral coordination of drainage management in Semarang is still not optimal. It is also found that coordination indicators awareness of the importance of coordination, the competence of human resources involved, and continuity planning has been running well, but for communications and agreements; commitment; and initiative in coordinating the management of the drainage in Semarang is not optimal. Moreover, some factors in the intersectoral coordination as employment and discipline has been running well, but the for unity of action and the division of labor in the management of the drainage is not optimal. Based on the results, it can be concluded that in general the intersectoral coordination of drainage management in Semarang is quite good, although there are some indicators / dimensions that must be enhanced and improved. Researcher suggest to opmimalize the use of ICT, manufacturing of manual procedure, more creative and initiative leader, to increasing quantity of human resources, establishment of drainage management agency, in cooperation with the private sector, and resource optimization.